RF41 LIQUID BIOPSY FORCARDIAC TUMORS - G. Santise; D. Maselli; C. Mignogna; K. PIrrone; V. Mollace; G. Donato; N. Malara (Journal of Cardiovascular Medicine, 2018)
Background: Cardiac tumors are a small percentage of cardiac disease. They are mostly identified and diagnosed by echocardiography. Anyway, histological diagnosis can be obtained after surgical resection. The possibility of knowing the nature of the tumor before the surgery would be beneficial to plan the appropriate strategy. We applied a specific liquid biopsy procedure on peripheral blood, to verify the hypothesis that cells becoming from the tumor circulate in the bloodstream and can be isolated and cultured. Method: In six patients with echocardiographic diagnosis of cardiac mass, we collected 5 ml of peripheral blood the day before surgery. The blood was processed following the procedure previously reported 1-2 . Cellular suspension isolated from the blood were seeded on chamber slides and cultivated for 14 days, and then the cellular growth were analyzed by cytometry and cells morphology by hematoxylin eosin staining. The results have been compared with the histological diagnosis made by two blinded pathologists on the surgical specimen. Results: In two cases the diagnosis made with the liquid biopsy was cardiac mixoma, in two angiosarcoma and in the last two fibroelastome. The five patients were sent to surgery and the traditional histological diagnosis confirmed the results of liquid biopsy. Conclusion: The liquid biopsy appear to be safe and effective to reach a correct diagnosis. This can be useful to plan the correct strategy in case of cardiac masses. Reference 1. J Biol Regul Homeost Agents. 2014 Oct-Dec;28 (4):717-31. 2. J Transl Med. 2016 May 12;14 (1):133. doi: 10.1186/s12967-016-0876-y